Remaja Kristen di Era Digital: Strategi Konseling Menghadapi Krisis Identitas Akibat Media Sosial - Heintje Kobstan; Meily Kouwagam; Lita Patricia Lunanta (PADAMARA: Jurnal Psikologi dan Sosial Budaya, 2026)
This is an analysis of the identity crisis experienced by Christian adolescents within a digital ecology filled with social comparison, cyberbullying, sleep disruption, and Fear of Missing Out (FOMO). The background highlights numerous findings on how social media affects individual well-being. There are real psychosocial dangers, but also opportunities to enhance peer support and faith. The method used is a narrative-integrative review with a qualitative approach to literature from 2010–2025, sourced from academic publishers and databases like Google Scholar, PubMed, and Scopus. Additionally, theoretical synthesis from Erikson–Marcia, DSMM, I-PACE, and integrated Christian counseling practices are utilized. Risk mechanisms (e.g., upward social comparison, FOMO, cyberbullying, and displacement of offline activities) and protective factors (e.g., media literacy, supportive monitoring, faith communities) are discussed. The discussion then shifts to evidence-based intervention strategies, such as metric-based CBT, media literacy and algorithmic awareness, sleep hygiene, forgiveness interventions, and family-school-church digital  covenants. The "IDENTegrasi" counseling model, which ethically integrates psychological-spiritual interventions (informed consent) and maps identity status with digital risk assessments, is also outlined. The synthesis results show that this model can be effectively used for assessments, session planning, and monitoring outcomes (e.g., identity coherence, digital well-being, and community engagement). This study emphasizes the development of contextual media literacy and spiritual well-being measurement tools, as well as structured trials to assess the effectiveness of the model in schools and youth ministry. Limitations of the study include the lack of longitudinal data and the heterogeneity of contexts.